Students Creative Thinking With 4'R Applications in Procedure Text Project Based Learning - Dariman, Kusmiati (International Journal for Educational and Vocational Studies, 2019)
The application of 4 'R (Reading, Reciting, Reasoning, and aRithmetic) is very important to be applied in an integrated way in learning. The purpose of this study was to describe students 'creative thinking with the application of 4' R (Reading, Reciting, Reasoning, and aRithmetic) in project-based text learning. This study uses Classroom Action Research method. The research subjects were students of  grade VIIA Sabilillah Islamic Junior High School Malang. The results showed that students' creative thinking skills were still very low, namely 61.29%. Based on the facts found the learning process has not taken place optimally. Finally, after applying  4R (Reading, witing, Reasoning, and aRithmetic) in project-based  learning. Students 'creative thinking skills on average experienced an increase after improvements were made with the implementation of the 4' R and project-based learning. This can be shown in the increasing percentage of skills reaching an average of 77, 46% in the first cycle and increasing in the second cycle reaching a percentage of 96.77%.